(3aVGFd HjJ GdebOSs - (3eTQa Hf oenQnqLi Hf EHQGgje GdebOSj CHh GdeYGdj,J (B450 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe Jbi GdOjf CHh GdMSjf CMeO Hf MeRI Hf Ydi GdTGaYi QVi Gddg Yfg HjeOjfI OeTb MQSgG Gddg JYGdi , HJGQjN TgQ QLH SfI KdGK hYTQjf hNeSeGFI s
(3Vef eLehY , JQJjHgG (B: 6s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B113 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs